2017
DOI: 10.1242/dev.143479
|View full text |Cite
|
Sign up to set email alerts
|

ChIP-seq analysis of genomic binding regions of five major transcription factors in mouse epiblast stem cells that highlights a central role for ZIC2

Abstract: To obtain insight into the transcription factor (TF)-dependent regulation of epiblast stem cells (EpiSCs), we performed ChIP-seq analysis of the genomic binding regions of five major TFs. Analysis of in vivo biotinylated ZIC2, OTX2, SOX2, POU5F1 and POU3F1 binding in EpiSCs identified several new features. (1) Megabase-scale genomic domains rich in ZIC2 peaks and genes alternate with those rich in POU3F1 but sparse in genes, reflecting the clustering of regulatory regions that act at short and long-range, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…In the epiblast stem cells (EpiSCs) from which neural primordia are derived directly, SOX2 and ZIC2 are already highly expressed (Brons et al, ; Iwafuchi‐Doi et al, ; Tesar et al, ). However, in the EpiSCs, ChIP‐seq data indicate that the D1 sequence was already bound by ZIC2 but not by SOX2 in EpiSCs (GSM1924746 and GSM1924744, Matsuda et al, ), as shown using Integrative genomics viewer (Robinson et al, ) (Figure S3). It is possible that before the neural development starts, ZIC2 first binds to the D1 enhancer sites as a “pioneer factor” (Zaret & Mango, ) to recruit SOX2 in later neural development.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the epiblast stem cells (EpiSCs) from which neural primordia are derived directly, SOX2 and ZIC2 are already highly expressed (Brons et al, ; Iwafuchi‐Doi et al, ; Tesar et al, ). However, in the EpiSCs, ChIP‐seq data indicate that the D1 sequence was already bound by ZIC2 but not by SOX2 in EpiSCs (GSM1924746 and GSM1924744, Matsuda et al, ), as shown using Integrative genomics viewer (Robinson et al, ) (Figure S3). It is possible that before the neural development starts, ZIC2 first binds to the D1 enhancer sites as a “pioneer factor” (Zaret & Mango, ) to recruit SOX2 in later neural development.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, in the post‐implantation epiblast and anterior neural plate, Sox2 expression is completely dependent on the N2 enhancer that is located ~3 kb upstream of the gene. The N2 enhancer is activated by the combination of ZIC2, OTX2 and a POU factor (Iwafuchi‐Doi et al, , ), which reflects the GRN in the epiblast centered by the ZIC2‐OTX2 TF combination (Kondoh, ; Matsuda et al, ). Further, the Sox2 expression in the growing posterior end of the neural plate is regulated by the N1 enhancer regulated by the Wnt and fibroblast growth factor signal downstream TFs, which represent the major GRN in the neuro‐mesodermal progenitor population (Kondoh & Takemoto, ; Takemoto, Uchikawa, Kamachi, & Kondoh, ; Takemoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ESCs in this study were cultured under conditions that create the EpiSC state. Further work in this cell type also implicated ZIC2 as an important player in the transcriptional regulatory circuits in these cells (Matsuda et al, 2017). Moreover ZIC1 and ZIC2 have been shown to play a role much later in development in the context of the neuronal gene expression programme in cerebellar granule neurones (Frank et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…To investigate whether such a difference can be recapitulated on a genomic scale, we mined published nucleosome mapping and Sox2/Oct4 ChIP-seq data and interrogated the distributions of Sox2 and Oct4 binding sites relative to nucleosome locations ( Figure 7A). We first calculated the aggregate nucleosome-positioning score surrounding Sox2/Oct4 binding sites in mouse embryonic stem cells (mESCs) (Teif et al, 2012) and epiblast stem cells (mEpiSCs) (Matsuda et al, 2017). In both cell types, the average nucleosome occupancy across all Sox2 binding sites is much greater than that for all Oct4 binding sites ( Figure 7B), indicating that Sox2 binding sites are more enriched in nucleosome-occupied regions than Oct4 sites.…”
Section: Genome-wide Binding Preference Of Sox2 and Oct4 With Respectmentioning
confidence: 99%
“…ChIP-seq peak locations were then called using MACS2 (v. 2.1.2) using the same settings as previously described (defaults except genome size 1.87×10 9 , P-value threshold 10 -9 , and "--keep-dup" set to "auto") (Whyte et al, 2013). For mouse EpiSCs, ChIP-seq data were downloaded as BED intervals from the NCBI GEO (Oct4, GSM1924747; Sox2, GSM1924746) (Matsuda et al, 2017). We defined TF binding sites as locations conforming to the canonical binding motif within 200 bp of the respective ChIP-seq peak; tandem Sox2:Oct4 binding sites were defined as locations conforming to the composite motif within a 400-bp window centered on the overlap of the two ChIP-seq peaks.…”
Section: Structure Alignmentmentioning
confidence: 99%